Al-Qur’an Learning in Religious Education Institutions Analysis of Proces Results and Problems - Samudra, Mulya; Rahmi, Elvi; Sabri, Yuli (STIT Ahlussunnah Bukittinggi, 2022)
The problems faced by educational institutions in Indonesia generally involve quality, relevance, and management. The existence of this problem gives rise to problems in Islamic education. This research aims to determine teacher programs in improving Al-Quran reading and writing skills, forms of activities for implementing Al-Qur'an reading and writing learning, supporting and inhibiting factors for Al-Qur'an reading and writing learning in Al-Qur'an Education Parks in the area Pasir Jambak, Koto Tangah, Padan. This research uses descriptive qualitative methods. The data collection techniques used are observation, interviews, and documentation with data analysis through data reduction, data presentation, and drawing conclusions and verification. The results of this research can conclude that: The Al-Quran reading and writing program has been implemented well, this can be seen from the routine activities of reading and writing the Al-Quran carried out by the Islamic boarding school students. This learning activity is fully supported by human resources in the Al-Qur'an Education Park environment with the quality of knowledge and morals possessed by teacher figures so that it becomes motivation and a good source of information for the students, while there are inhibiting factors for the students in attending learning activities so that learning activities are delayed and not optimal. The results of this research can provide guidance for Al-Qur'an Education Park managers and can be used as initial data for future researchers in studying this problem in different contexts and issues.